Tapping into rhythm generation circuitry in humans during simulated weightlessness conditions - Solopova, Irina A.; Selionov, Victor A.; Sylos-Labini, Francesca; Gurfinkel, Victor S.; Lacquaniti, Francesco; Ivanenko, Yuri P. (Frontiers in Systems Neuroscience, 2015)
An ability to produce rhythmic activity is ubiquitous for locomotor pattern generation and modulation. The role that the rhythmogenesis capacity of the spinal cord plays in injured populations has become an area of interest and systematic investigation among researchers in recent years, despite its importance being long recognized by neurophysiologists and clinicians. Given that each individual interneuron, as a rule, receives a broad convergence of various supraspinal and sensory inputs and may contribute to a vast repertoire of motor actions, the importance of assessing the functional state of the spinal locomotor circuits becomes increasingly evident. Air-stepping can be used as a unique and important model for investigating human rhythmogenesis since its manifestation is largely facilitated by a reduction of external resistance. This article aims to provide a review on current issues related to the ‘locomotor’ state and interactions between spinal and supraspinal influences on the central pattern generator circuitry in humans, which may be important for developing gait rehabilitation strategies in individuals with spinal cord and brain injuries.